ESENSI ADAT KAWIN LARI (MERARIQ) DALAM MASYARAKAT SUKU SASAK DI DESA APITAIK KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR - Yeni Santi; Alda Heri Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The tradition of kawin lari (merariq) continues to be practiced and preserved in Apitaik Village, Pringgabaya District, East Lombok Regency, along with the accompanying processions and ritual stages observed within the Sasak community. This study adopts a normative legal research method, drawing on secondary legal materials and employing document-based data collection techniques (library research). The findings indicate that the persistence of the merariq tradition in Apitaik Village is shaped by multiple interrelated factors. These include its recognition as an inherent component of customary law, the intention to safeguard and perpetuate ancestral cultural heritage, the absence of parental consent for marriage, its role in affirming a man’s social standing, and economic considerations.Within the Sasak community, the merariq process unfolds through a sequence of distinct stages: Beleqet (courtship or approach), Selabar (eloping with the woman), Nyeserang (negotiations between the families), Sorong Serah (formal handover ceremony), Ijab Kabul (marriage contract), Nyongkolan (wedding procession), and, finally, Reception and Thanksgiving (a celebratory event marking the conclusion of the marriage rites). By examining both the legal and cultural dimensions of merariq, this research contributes to a deeper understanding of the interplay between customary traditions and contemporary societal values within the Sasak community of East Lombok.